2012
DOI: 10.2175/106143012x13347678384161
|View full text |Cite
|
Sign up to set email alerts
|

Field Characterization of External Grease Abatement Devices

Abstract: BSTRACT: This study characterized some of the physical and chemical features of large outside field grease abatement devices (GADs). 24-hour measurements of several food service establishments' (FSEs') influent GAD fiowrates indicated highly intermittent conditions with hydraulic retention times (HRTs) that exceeded the common recommendation (30 minutes) by two to five times. Investigation into the chemical characteristics of GADs indicated highly variable influent and effluent fat, oil, and grease (FOG) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The variability of the GTW could also be due to the type of grease abatement device used at the restaurant or cooking facility. It was observed that FOG layers typically remained constant for different types of grease traps; however, food solids can accumulate in the first compartment or be transported depending on the inlet tee . The variability in inlet type at the various food services could explain some of the variability seen with the sediment layer.…”
Section: Resultsmentioning
confidence: 99%
“…The variability of the GTW could also be due to the type of grease abatement device used at the restaurant or cooking facility. It was observed that FOG layers typically remained constant for different types of grease traps; however, food solids can accumulate in the first compartment or be transported depending on the inlet tee . The variability in inlet type at the various food services could explain some of the variability seen with the sediment layer.…”
Section: Resultsmentioning
confidence: 99%
“…All laboratory GI reactors in this study were operated with an intermittent flow pattern that involved pumping artificial wastewater through the reactors twice a day to simulate the two diurnal peak flows of real GIs. 12 The two pumping events lasted for one hour each and were separated from each other by five hours. All reactors were operated for 60 days in the dark and at room temperature (23-25 °C).…”
Section: Reactor Operation and Sample Collectionmentioning
confidence: 99%
“…First of all, the sizing of GI for a given wastewater stream could result in different hydraulic retention times (HRTs), which in the field typically ranges from 0.3 to 4.4 days. 12 Different HRTs may affect the quantity of LCFAs produced by microbial activities within GIs, as the incubation time often controls the production of bacterial lipases that catalyze oil hydrolysis. 7,13 Different HRTs may also affect the LCFA composition in GIs, as faster biodegradation of unsaturated LCFAs than that of saturated LCFAs was previously observed in an activated sludge process.…”
Section: Introductionmentioning
confidence: 99%